KRISIS UKRAINA 2022: Apa Artinya Bagi Hubungan Sino-Rusia - Yuliantoro, Nur Rachmat; Bromokusomo, Leonard Patrick (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
The onset of the Russo-Ukrainian conflict in February 2022, commonly referred to as the 2022 Ukraine crisis, has had a notable impact on the dynamics of Sino-Russian relations. In light of Russia encountering a severe reaction from the global community, it is anticipated that China will assume a mitigating role, owing to their amicable bilateral ties throughout the preceding decade. This study investigates the potential for increased assertiveness in China’s response to the invasion and the resulting implications for their ties. It examines the ramifications of the crisis on Sino-Russian relations, considering the elements that contribute to either the change or continuity of these interactions. It does so by referencing a short historical account of the relations and power dynamics among the relevant actors, employing a realist perspective. The analysis of this study reveals that China has departed from its initially neutral position during the crisis, indicating its capacity to assume the responsibilities associated with becoming a major global power. Nevertheless, their bilateral relations may be advantageous to China with time, primarily due to Russia’s increasing economic reliance and China’s potential for enhancing its global standing.